WORD ORDER IN BOGOR DIALECT SUNDANESE: A STUDY OF SYNTACTIC TYPOLOGY - Parasian, Nehemia Anugrah; Mulyadi, M (Linguistics and Literature Journal, 2025)
This study aims to examine in depth the word order in Sundanese in Bogor dialect, focusing on sentence structure patterns commonly used by native speakers in various communication contexts. The method used in this research is descriptive qualitative. The translation results will be analysed to see the typology of the Bogor dialect Sundanese language in word order. The results of data analysis will be presented in the form of conclusions to answer what and how the typology of Sundanese language of Bogor dialect in word order. From the results of data and analysis, it is found that the Bogor dialect Sundanese language follows the most dominant S + V + O pattern, especially in ordinary declarative sentences. Negative sentences have the pattern S + NEG + V + O. Command sentences have the pattern V + O. Interrogative sentences have the pattern Question word + Rel + V + O. Passive sentences have the pattern O - Asp - Passive V - Agent. Aspectual declarative sentences have the pattern S - Asp - V – O.Keywords: Bogor dialect, Sundanese language, syntactic typology, word order